Serum levels of irisin and nesfatin-1 in multiple sclerosis - Mustafa ALTAŞ; Ali Ulvi UCA; Turan AKDAĞ; Faruk Ömer ODABAŞ; Osman Serhat TOKGÖZ (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: Multiple sclerosis (MS) is an inflammatory and neurodegenerative autoimmune chronic neurological disease. Currently, there are no effective serum biomarkers to verify MS diagnosis, to assess disease prognosis, and evaluate response to MS treatment. Objective: The present study is a preliminary assessment of irisin and nesfatin-1 serum levels in patients with relapsing- remitting MS (RRMS). Methods: A total of 86 participants, 42 patients with RRMS diagnosis and 44 healthy controls were included in the study. The serum irisin and nesfatin-1 parameters of the patients and control group members were analyzed. Results: Irisin and nesfatin-1 levels of the RRMS patients were significantly lower than the controls (z: -3.82, p<0.001; z: -4.79, p<0.001, respectively) The cut-off level of irisin is 10.390 (ng/mL) (sensitivity: 84.1%, specificity: 71.4%, AUC: 0.800), and the cut-off level of nestatin-1 is 7.155 (ng/mL) (sensitivity: 68.2%, specificity: 64.3%, AUC: 0.739) in the ROC analysis. For these cut-off levels in the case-control groups, the lower irisin and nesfatin-1 levels are the independent variables for MS patients (OR 9.723, 95%CI 2.884-32.785, p<0.001; OR 3.992, 95%CI 1.336-11.928, p<0.001) respectively. Conclusion: The present study revealed lower irisin and nesfatin-1 levels in patients with RRMS. These findings suggest that the decreased levels of irisin and nesfatin-1 peptides may contribute to MS pathogenesis such as inflammation, oxidative stress, and apoptosis in MS, leading to demyelination, axonal damage with neuronal loss, and gliosis.